2016
DOI: 10.1007/s11164-016-2577-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural and textural features of TiO2/SAPO-34 nanocomposite prepared by the sol–gel method

Abstract: This paper focuses on the synthesis of nanocomposite materials TiO 2 /SAPO-34 using the sol-gel method, which involves preparing a mixture between as-synthesized or calcined SAPO-34 zeolite and TiO 2 gel under hydrothermal crystallization and then calcined at 400 °C for the formation of TiO 2 anatase phase. The structural and textural features of the obtained materials were determined by various physico-chemical techniques such as thermogravimetric analysis (TGA), X-ray diffraction (XRD), scanning electronic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…These results have matched well with the characteristic alignments of anatase form of TiO 2 (JCPDS no. 01–086‐1157) . The XRD results in case of 2:1 ratio of TiO 2 /SAPO‐35 composite clearly showed the domination of TiO 2 patterns over the SAPO‐35 patterns, this is due to the excellent dispersion of TiO 2 on the surface of SAPO‐35, as a consequences the SAPO‐35 crystal patterns are absent.…”
Section: Resultsmentioning
confidence: 92%
“…These results have matched well with the characteristic alignments of anatase form of TiO 2 (JCPDS no. 01–086‐1157) . The XRD results in case of 2:1 ratio of TiO 2 /SAPO‐35 composite clearly showed the domination of TiO 2 patterns over the SAPO‐35 patterns, this is due to the excellent dispersion of TiO 2 on the surface of SAPO‐35, as a consequences the SAPO‐35 crystal patterns are absent.…”
Section: Resultsmentioning
confidence: 92%
“…Zeolites or zeolitic materials, a big family of porous materials, show many distinct properties, such as framework component controllability and high adsorption. Aluminosilicalites and aluminosilicophosphates (SAPOs) are usually used as catalysts in cracking, isomerization, and alkylation reactions, such as SAPO-34 [5,6], Y-type [7,8], and ZSM-5 [9]. Recently, it was found that aluminosilicalites and SAPOs also exhibited photocatalytic activity for the charge transfer excited state of [Al 2+ –O − ]* under UV illumination, which has been demonstrated in some literature [9,10].…”
Section: Introductionmentioning
confidence: 99%